Transformasi Digital di Belitung: Bagaimana Mobile Banking Merubah Cara PNSD Bertransaksi - Fastri Fatmawati; Abdul Rohman (Owner : Riset dan Jurnal Akuntansi, 2025)
Finding out how the TAM variable affects regional civil servants' adoption of mobile banking in Belitung Regency is the aim of this study. A theoretical framework model is developed employing five variables; perceived usefulness, perceived ease of use, education level, attitude toward using, and behavioral intention. Belitung Regency's regional civil servants are the subject of this study. Structural Equation Modeling using WarpPLS 8.0 is the data analysis technique. Convenience sampling was used in this study to gather information from 139 respondents, who were Belitung Regency civil servants who utilize the Bank Sumsel Babel mobile. According to the study's findings, attitudes toward use were influenced by perceived usefulness and perceived ease of use, but not education level. Perceived ease of use and attitudes toward the Bank Sumsel Babel mobile application were the main factors influencing the behavioral intention of regional civil servants in Belitung Regency to adopt mobile banking; perceived usefulness and education level had no effect. The study's findings have consequences for banks, particularly Bank Sumsel Babel who should keep enhancing their mobile banking offerings to attract more users of mobile banking.